The Testability of Distributed Real-Time Systems - Schütz, Werner. (The Springer International Series in Engineering and Computer Science, 1993)
BY H. KOPETZ A real-time computer system must provide the intended service in two di mensions: the functional (value) dimension and the temporal dimension. The verification of a real-time system implementation is thus necessarily more com plex than the verification of a non-real-time system which has to be checked in the value dimension only. Since the formal verification techniques of temporal properties have not yet matured to the point where these techniques can be used in practical system development, systematic design and testing are the only alternatives for the development of dependable real-time systems. At present, up to and more than fifty percent of the development eff'ort of complex real-time computer systems is spent on testing. The test activities are thus a significant cost element in any real-time system project. The attack on this cost element has to proceed from two fronts: the design for testability and the development of a systematic test methodology supported by an appropriate tool set. This book covers both of these topics.